Skilled but unaware of it: Occurrence and potential long-term effects of females' financial underconfidence - Christina E. Bannier; Milena Schwarz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We find strong gender- and education-related differences in the distribution of actual and perceived financial sophistication: Whereas financial literacy rises in formal education, confidence increases in education for men but decreases for women. We show that the financial decisions of highly-educated men benefit strongly from this excess confidence, while the underconfidence of highly-educated women, in contrast, impairs their long-term financial planning.
Keywords: D91; G11; D83; J26; 330